Optochemical Control of Bacterial Gene Expression: Novel Photocaged Compounds for Different Promoter Systems. (2nd December 2021) - Hogenkamp, Fabian; Hilgers, Fabienne; Bitzenhofer, Nora Lisa; Ophoven, Vera; Haase, Mona; Bier, Claus; Binder, Dennis; Jaeger, Karl‐Erich; Drepper, Thomas; Pietruszka, Jörg
Abstract: Photocaged compounds are applied for implementing precise, optochemical control of gene expression in bacteria. To broaden the scope of UV‐light‐responsive inducer molecules, six photocaged carbohydrates were synthesized and photochemically characterized, with the absorption exhibiting a red‐shift. Their differing linkage through ether, carbonate, and carbamate bonds revealed that carbonate and carbamate bonds are convenient. Subsequently, those compounds were successfully applied in vivo for controlling gene expression in E. coli via blue light illumination. Furthermore, benzoate‐based expression systems were subjected to light control by establishing a novel photocaged salicylic acid derivative. Besides its synthesis and in vitro characterization, we demonstrate the challenging choice of a suitable promoter system for light‐controlled gene expression in E. coli . We illustrate various bottlenecks during both photocaged inducer synthesis and in vivo application and possibilities to overcome them. These findings pave the way towards novel caged inducer‐dependent systems for wavelength‐selective gene expression. Abstract : Novel optochemical tools for controlling gene expression in E. coli were investigated. Six photocaged carbohydrates with redshifted absorption and a photocaged salicylic acid derivative were synthesized, photochemically characterized and applied in vivo for light‐mediated target gene expression. The potential challenges during the establishment of a new optochemically controllable system and sufficient solutions are discussed in detail.